Towards a Cognition-Centered Personalization Framework for Cultural-Heritage Content - Raptis, George E.; Fidas, Christos A.; Katsini, Christina; Avouris, Nikolaos M. (Extended Abstracts of the 2018 CHI Conference on Human Factors in Computing Systems, 2018)
Comprehension of visual content is linked with the visitor's experience within cultural heritage contexts. Considering the diversity of visitors towards human cognition, in this paper, we aim to investigate whether cognitive characteristics are associated with the comprehension of cultural-heritage visual content. We conducted a small-scale eye-tracking study in which people with different visual working memory capacity participated in a gallery tour and then they were assessed towards exhibit comprehension. The analysis of the results revealed that people with low visual working memory faced difficulties in comprehending the content of the gallery paintings. In this respect, we propose a cognition-centered cultural heritage framework, aiming to provide personalized experiences to visitors and help them improve the content comprehension.
Keywords: cultural heritage; human cognition; individual cognitive differences; personalization; virtual gallery exhibition; visual working memory